METHOD FOR ELECTRONIC MAP CREATING FOR COMPARTMENT NETWORK OF FORESTRY ENTERPRISE USING SATELLITE TECHNOLOGY IN GEODETIC WORKS - Bogomolov, V. V.; Borysenko, O. I.; Zhadan, I. V.; Polupan, A. V. (Forestry and Forest Melioration, 2018)
Forestry enterprises make more demands to quality and accuracy of cartographic materials. This is due to such factors as strong requirements of audit institutions to the accuracy of forest area allocation, disputes with adjacent land users, using modern surveying equipment during works. The only way to meet the needs is to survey in the field. So, in our opinion, in the first place it is necessary to carry out survey of land use boundaries and compartment network. The process of making precise electronic map of compartment network includes the following stages: Analysis of present materials and preparing project points for surveying. Surveying project points on intersections of compartment lines and compartment lines with land-use boundaries using geodetic instruments. Processing data in cameral conditions involving State Geodetic Reference Frame or commercial GNSS network. Making new compartment network based on surveying data. Delivering the results to forest management enterprises for further using. It has become obvious that the approaches to create forest maps by forest management cannot fully satisfy demands of forestry enterprises during forest area allocation. Not precise enough electronic maps as a result of forest management works do not provide two main advantages that can be provided by the accurate ones namely. - Precise overlapping results of surveying on forest management plan without additional reference points. - Accurate relocation of subcompartments in situ by coordinates. The necessary prerequisites for creating electronic maps as a precise basic map of forestry enterprise are as follows. Survey of the territory of forestry enterprise using modern GPS-receivers with the help of GNSS network before conducting basic forest management works. Checking and correcting remote sensing data that will be involved in forest management works. Using special software for interpretation of remote sensing data on a preparatory phase of forest management works.